The truth about truancy - Whitney, Ben. (London : Philadelphia : Kogan Page, 1994)
Presenting information from the perspective of the professional education welfare officer, the author provides a clear summary of UK law relating to truancy, and offers advice both on the new policies that schools and Education Authorities should adopt, and the role that teachers can play.
Includes bibliographical references and index.
Keywords: School attendance -- Great Britain; School attendance -- Law and legislation -- Great Britain